2021
DOI: 10.1073/pnas.2015416118
|View full text |Cite
|
Sign up to set email alerts
|

An unconventional role of an ASB family protein in NF-κB activation and inflammatory response during microbial infection and colitis

Abstract: Nuclear factor κB (NF-κB)–mediated signaling pathway plays a crucial role in the regulation of inflammatory process, innate and adaptive immune responses. The hyperactivation of inflammatory response causes host cell death, tissue damage, and autoinflammatory disorders, such as sepsis and inflammatory bowel disease. However, how these processes are precisely controlled is still poorly understood. In this study, we demonstrated that ankyrin repeat and suppressor of cytokine signaling box containing 1 (ASB1) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Usually, seven lysine residues and an N‐terminus of ubiquitin are served for protein ubiquitination, including K6, K11, K27, K29, K33, K48, K63 and M1 24 . The role of K48 and K63 is well studied for facilitating or preventing proteasomal degradation of the substrate protein, respectively 34–38 . K11‐linked chains are often accompanied by the K48 counterparts in regulating protein degradation involved in cell mitosis, 39 as well as protein expressions of type 1 interferon 40 and hypoxia‐inducible factors HIF1α and HIF2α 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, seven lysine residues and an N‐terminus of ubiquitin are served for protein ubiquitination, including K6, K11, K27, K29, K33, K48, K63 and M1 24 . The role of K48 and K63 is well studied for facilitating or preventing proteasomal degradation of the substrate protein, respectively 34–38 . K11‐linked chains are often accompanied by the K48 counterparts in regulating protein degradation involved in cell mitosis, 39 as well as protein expressions of type 1 interferon 40 and hypoxia‐inducible factors HIF1α and HIF2α 41 .…”
Section: Discussionmentioning
confidence: 99%
“… 24 The role of K48 and K63 is well studied for facilitating or preventing proteasomal degradation of the substrate protein, respectively. 34 , 35 , 36 , 37 , 38 K11‐linked chains are often accompanied by the K48 counterparts in regulating protein degradation involved in cell mitosis, 39 as well as protein expressions of type 1 interferon 40 and hypoxia‐inducible factors HIF1α and HIF2α. 41 Although Lys11‐linked Ub chains have been regarded as proteasomal signals in cell cycles in APC/C signaling pathway, 42 recent evidence has shown that homotypic K11 linkages do not direct the substrate for proteasomal degradation, instead, the heterotypic K11 linkages are efficient for targeting proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction or death of these cells are closely involved in sepsis-AKI (22)(23)(24). During the host's defense against infection, macrophages play a central role in innate immunity (25,26), recognizing pathogen-associated molecular patterns (PAMPs) and/or host-derived damage-associated molecular patterns (DAMPs) through pattern recognition receptors (27,28). PAMPs and/or DAMPs released from damaged tissues activate and promote the pro-inflammatory phenotype (M1) of macrophages, leading to the release of pro-inflammatory cytokines such as interleukin (IL)-1, IL-6, tumor necrosis factor-α (TNF-α), chemokines and reactive oxygen species (ROS), which cause damage to the kidney tissue (29,30).…”
Section: Macrophages Vascular Endothelial Cells and Renal Tubular Epithelial Cells Are Involved In Sepsis-akimentioning
confidence: 99%
“…According to the ROC curve, ASB1, UBB, and MKRN1 can effectively act as potential diagnostic markers for distinguishing samples of Staphylococcus aureus infection from healthy counterparts. ASB1, a member of the ASB family, acted as a positive regulator of NF-κB– and MAPK-mediated inflammatory signaling pathways [ 39 ]. Appropriate inflammatory response helps immune cells fight microbial infections while excessive inflammatory response can damage tissues and cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate inflammatory response helps immune cells fight microbial infections while excessive inflammatory response can damage tissues and cells [ 40 ]. The study pointed that ASB1 deficiency protected mice from LPS- or bacteria-induced death by inhibiting inflammation [ 39 ]. Therefore, we speculated that inhibition and down-regulation of ASB1 in the late stage of infection can against the inflammatory injury induced by Staphylococcus aureus .…”
Section: Discussionmentioning
confidence: 99%